The relationship between human resource management practices, workplace spirituality and employee loyalty in Nigeria - Tanwa, Owodunni Oluwakemi (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
Human resource management (HRM) practices scope has been broadened to include workplace spiritualty (WS) dimension in order to increase employee loyalty to organization. Employee loyalty plays a significant role in the organizational development as well as economic growth around the word. The main purpose of this study is to investigate the relationship between human resource management practices (HRMP), workplace spirituality (WS) and employee loyalty (EL) in Nigeria public sector. A proposed human resource management practices model that embed workplace spirituality measures were formulated and tested on employee loyalty. This study adopts quantitative research approach. Survey, using questionnaire, was conducted to obtained data from 500 public sector employees in Lagos state Nigeria. Structural Equation Modeling analysis using AMOS version 22 was conducted to determine the direct and indirect effects of HRM on employee loyalty. The findings reveal that there is a strong causal relationship between HRM practices and employee loyalty in Lagos state public sector. The findings also show the mediating effect of workplace spirituality on the relationship between HRM practices and employee loyalty. The study also establishes valid measures for workplace spirituality and employee loyalty constructs. It is evident from the findings that workplace spirituality is an underlying factor to reckon with in motivating employee to be loyal to their organization. Hence, this study supports the use of workplace spirituality as one of human resource management practices dimension in organization. This study recommends that future research should consider using longitudinal mixed method research design to study relationship between HRM practices, workplace spirituality and employee loyalty. Thus, findings of this research have undoubtedly created pathway for future research in human resource management.